Bone healing at bicortically installed implants with different surface configurations. An experimental study in rabbits. Issue 3 (15th September 2014) - Caneva, Marco; Lang, Niklaus P.; Calvo Guirado, José Luis; Spriano, Silvia; Iezzi, Giovanna; Botticelli, Daniele
Abstract Objective To study the sequential healing at bicortically installed implants with surface modifications by the use of fluoroboric acid and/or H2O2. Material and methods Twenty‐eight albino New Zealand rabbits were used. Two recipient sites were prepared in the tibiae bilaterally, one in the metaphysis and the second in the diaphysis regions. Four implants with different surface characteristics were randomly installed with bicortical stabilization: (i) sandblasted and acid‐etched; (ii) same surface as i, but with a substitution of the hydrofluoric acid with fluoroboric acid; (iii) same surface as i, additionally treated with H2O2; and (iv) same surface modified as ii, additionally treated with H2O2. The animals were killed after 5, 8, 15, and 30 days. Ground sections were prepared for histological analyses. Results No statistically significant differences in osseointegration were found among various surfaces at any of the healing periods. A higher degree of osseointegration was observed at the implants placed in the metaphysis compared to those placed in the diaphysis, especially during early healing. A higher degree of osseointegration was found at sites with proximity to compact (cortical) bone when compared to the middle portion of the implants, especially in the diaphysis region. Conclusions Surfaces modified with different acids or H2O2 resulted in similar osseointegration compared to a standard sandblasted and acid‐etched surface. The portion of the bicortically installed implants in close contact with the cortical compartment presented a higher percentage of osseointegration compared with the region in contact with the bone marrow compartment.